Peran Wanita Karir dalam Keluarga: (Studi Eksistensi Wanita Karier dalam Keluarga di Desa Balunijuk) - Herdiyanti Herdiyanti (Society, 2018)
The existence of women over the time in transition or shift from traditional to modern. The role of the woman who used to be adopted only capable of working in the domestic realm, but this time she is able to develop itself in the public sphere. This raises the existence of variants of interest, between the domestic and the public sphere. This study used a qualitative research method with case study approach. The theory used in this research is by using the concept of rational choice of James Coleman. The purpose of this research is to describe the existence of a career woman in the family. These results indicate that the existence of career women in the public sphere in the family recognized for their collective agreement concluded between career women with families. Mainly deal agreed with her husband and children. But the deal does not diminish the responsibility of working women in the domestic sphere. Career woman in the village Balunijuk not neglect its role as a housewife and also as a career woman. Role between domestic and public balanced and collaborate.